O artista popular e o contrato: lógicas divergentes nas produções musicais - Mariana Mont\u2019Alverne Barreto Lima (Ciências Sociais Unisinos)
The means of producing, distributing and consuming recorded music have been quickly changing since the end of the 20th century. Many investigations in different areas of the Human Sciences aimed at explaining and interpreting these means. The present article takes as its empirical object a work contract of “onerous assignment of fixed interpreta-tion” made between a Brazilian musical artist, João do Vale, and a big record label, CBS, in the 1980s. It shows how this juridical document, which is an institutional form of specific social bonds, reveals the strategy of a hegemonic business model of distribution in that period and how the dispositions of the agents involved in that process adjusted perfectly to that order. The text builds on the hypothesis that the conclusion of this sales contract shows the mark and domination of the phonographic field, of its organization and its functioning, considering bot the label and the artist.